Garage days - Proyas, Alex, 1963-; Proyas, Alex, 1963-; Gurry, Kick; Miranda, Pia; Stange, Maya (20th Century Fox Home Entertainment, 2003)
Ένα φρενήρες ταξίδι στην καρδιά του αυστραλέζικου ροκ εν ρολ γεμάτο ναρκωτικά, μουσική και ταχύτητα.